2019
DOI: 10.1103/physreva.99.012519
|View full text |Cite
|
Sign up to set email alerts
|

Antisymmetrized geminal powers with larger chemical basis sets

Abstract: In previous research, we tested the wave function format of a linear combination of several antisymmetrized geminal power states. A numerical problem in the geminal matrices was noted, which made the total energies of electronic systems with large numbers of electrons unstable. The underlying cause was found to be the large cancellation term in the geminal power series. We have obtained a new format to resolve this problem for the case of total energies and partly for the firstorder derivatives within the anti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 40 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…As a result, the energy obtained for the system of the water molecule with STO-3G basis set that we used in ref. [36] came closer to the exact value. Table I shows the result with complex parameters.…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…As a result, the energy obtained for the system of the water molecule with STO-3G basis set that we used in ref. [36] came closer to the exact value. Table I shows the result with complex parameters.…”
Section: Resultsmentioning
confidence: 54%
“…Here, the result with real parameters and the full-CI result was taken from ref. [36]. We observed that after changing the parameters to be complex, the resulting energy is closer to the exact energy.…”
Section: Methodsmentioning
confidence: 68%
See 2 more Smart Citations
“…In this paper, we explore an alternative perspective. Rather than writing the wave function in terms of AGP and operators that replace geminals, we write the wave function as a linear combination of AGPs (LC-AGP), 4,11,12 which has the advantage that matrix elements between two different AGP states are simple. LC-AGP is related to the symmetric tensor decomposition of the exact wave function, 4,11 and non-orthogonal construction of AGP bases is natural due to the close connection between AGPs and elementary symmetric polynomials (ESPs).…”
Section: Introductionmentioning
confidence: 99%